Counseling and Dissemination of Mapping Potential Sources of Processed Waste in Cijulang District, Pangandaran. - AULIA ANDHIKAWATI; REGA PERMANA (Unpad Press, 2023)
Pangandaran has potential for developing multisectoral fisheries and marine science, such as marine tourism, aquaculture, marine culture, fishing, and fishery processing. The increase of fishery potential is followed by the development of the fishery product technology which is spread ini every sub district both on a large scale or houshold scale in the form of micro, small, and medium enterprises. The development of fishery based products has the potential to be implemented in Pangandaran. The development of fishery processing activities also indicates an increase in the potential for solid or liquid waste production. In order for fishery processing activities in Pangandaran always sustainable with zero waste principle, structured information is needed. There are three Poklahsar in Parigi District that produce salted fish, nuget, and jambal salted fish. The average total volume of waste is less than 20 kg/ month.